Hubungan Tingkat Stres Terhadap Mekanisme Koping Pada Retaker Profesi Ners Di Universitas Bina Bangsa Getsempena Banda Aceh - Syarifah Masthura; Nanda Desreza; Tasyani Simah Bengi (Jurnal Anestesi, 2023)
Stress is a stimulus or situation that causes distress and can create physical and psychological demands on a person. Nursing professional education is an advanced program from students to professional nurses, Retaker is a candidate who has participated in Ukom more than once where students who experience this repeatedly will cause stress so it is necessary to overcome these problems with a coping mechanism to find out the extent of the stress experienced that student. The purpose of this study was to determine the relationship between stress levels and coping mechanisms in nursing professions at Bina Bangsa University Getsempena Banda Aceh in 2023. By using a descriptive correlational research type with a cross-sectoral study approach design with a population of 48 respondents, the technique used in This research uses total sampling technique. This research was conducted on January 18-24 2023 with univariate and bivariate analysis. The results showed that of the 48 respondents who had moderate stress, there were 24 people (82.8%), while those who were heavily stressed were 4 people (13.8%), and those who experienced mild stress were 1 person (0%) with a p value 0.048, so there is a relationship between the level of stress on coping mechanisms in professional nurses. It is hoped that all students will increase their knowledge by digging up information about stress levels and improving coping mechanisms in dealing with UKOM.